2010
DOI: 10.1111/j.1365-2044.2009.06208.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for proximal femoral fracture in the UK: first report from the NHS Hip Fracture Anaesthesia Network*

Abstract: The aim of this audit was to investigate process, personnel and anaesthetic factors in relation to mortality among patients with proximal femoral fractures. A questionnaire was used to record standardised data about 1195 patients with proximal femoral fracture admitted to 22 hospitals contributing to the Hip Fracture Anaesthesia Network over a 2-month winter period. Patients were demographically similar between hospitals (mean age 81 years, 73% female, median ASA grade 3). However, there was wide variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 15 publications
3
52
0
Order By: Relevance
“…Nationally, as 50% of hip fracture repairs are performed under general anaesthesia [11], we estimate that anaesthesia for hip fracture repair costs the UK £18 million annually. Yet in a questionnaire of anaesthetic intent for hip fracture repair, Sandby-Thomas et al [23] found that 72% of 155 trauma anaesthetists preferred regional anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Nationally, as 50% of hip fracture repairs are performed under general anaesthesia [11], we estimate that anaesthesia for hip fracture repair costs the UK £18 million annually. Yet in a questionnaire of anaesthetic intent for hip fracture repair, Sandby-Thomas et al [23] found that 72% of 155 trauma anaesthetists preferred regional anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Congestive heart failure, myocardial infarction, pneumonia and pulmonary embolism are the most common causes of death [2,36,48,49]. As demonstrated in Table 3, most publications report overall long-term mortality to be low (<8%) with the authors stating, that this is not affected by anaesthetic technique (evidence level I-III; I: n=2) [2,5,10,25,36,37,41,43,44,46,48,49,68,69]. Because the follow-up periods ranged widely from "early death" to "hospital mortality" and "different time periods up to 1 year", this review defines short-term mortality as "mortality ≤1 month" and long-term mortality as "mortality from 3-month up to 1 year".…”
Section: Mortalitymentioning
confidence: 99%
“…Many clinicians declare a preference for regional over general anaesthesia [10]. Nevertheless, more than two thirds of orthopaedic surgeons surveyed in a trial conducted in North America and Europe felt the type of anaesthesia was of little or no importance as a predictor of outcome after femoral neck fracture surgery [11].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, professional guidelines [3][4][5] are unable to recommend one technique over the other with confidence, such that a wide spectrum of techniques continue to be used by anaesthetists [6]. This may explain in part why 30-day postoperative mortality has remained static at approximately 8% for the last five years in spite of national quality improvement initiatives, including data collection and publication by the National Hip Fracture Data-base [7] and 'best practice' tariff uplifts related to performance targets [8].…”
Section: Introductionmentioning
confidence: 99%